Virtue Signals - Deivis Angeli; Matt Lowe (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study whether tweets about racial justice predict the offline behaviors of nearly 20,000 US academics. In an audit study, academics that tweet about racial justice discriminate more in favor of minority students than academics that do not tweet about racial justice. Racial justice tweets are more predictive of race-related political tweets than political contributions, suggesting that visibility increases informativeness. In contrast, the informativeness of tweets is lower during periods of high social pressure to tweet about racial justice. Finally, most graduate students mispredict informativeness, more often underestimating than overestimating, reducing the welfare benefits of social media.
Keywords: C93; D91; I23; J15; J71; D83; 330; virtue signals; social signalling; discrimination; audit experiment; political behavior